Studi Kelayakan Bisnis Bimbingan Belajar Anak Hebat (AHE) Cabang Tegalsuruh Kabupaten Pekalongan - Jamila, Dinda Hasanatul (CV. Kalimasada Group, 2023)
The tutoring institution that is now quite well-known in the community is Anak Terbat. Students who study in this tutoring are preschool children, namely children from the age of 4.5 7 years. In general, the students who are tutored in this study are children who are still in playgroup, kindergarten group A and group B kindergarten. Non-financial methods include technical aspects, market aspects and marketing aspects, organizational and juridical aspects, management aspects and economic aspects. The method used in this research is qualitative method. The approach in this study used field research by directly observing the object under study and through interviews with teachers. In addition, this study also uses secondary data with literature articles on Great Children's Tutoring (AHE). The Feasibility Analysis of Market and Marketing Aspects of the Great Children's Tutoring shows that the prospects for the development of the Great Children's tutoring business are very good. This can be seen from the number of units which reach more than 3,000 units and are spread in almost all provinces in Indonesia. In addition, Great Children's Tutoring also applies different learning classes, namely private classes and reading classes which are the advantages of this tutoring. In the human resource aspect, Great Children's Tutoring also pays attention to the quality of the teacher's performance. And the results of financial analysis using the payback period show that the Tegalsuruh branch of the Great Child tutoring (AHE) takes 3 months and 10 days to return its capital